Decellularized heart ECM hydrogel using supercritical carbon dioxide for improved angiogenesis - Seo, Yoojin; Jung, Youngmee; Kim, Soo Hyun (ELSEVIER SCI LTD, 2018)
Initial angiogenesis within the first 3 days is critical for healing ischemic diseases such as myocardial infarction. Recently, decellularized extracellular matrix (dECM) has been reported to provide tissue derived ECM components and can be used as a scaffold for cell delivery for angiogenesis in tissue engineering. Decellularization by various detergents such as sodium dodecyl sulfate (SDS) and triton X-100 can remove the cell nuclei in tissue organs. However, this leads to ECM structure denaturation, decreased presence of various ECM proteins and cytokines, and loss of mechanical properties. To overcome these limitations, in this study, we developed a supercritical carbon dioxide and ethanol co-solvent (scCO(2)-EtOH) decellularization method, which is a detergent-free system that prevents ECM structure disruption and retains various angiogenic proteins in the heart dECM, and tested on rat heart tissues. The heart tissue was placed into the scCO(2) reactor and decellularized at 37 degrees C and 350 bar. After scCO(2)-EtOH treatment, the effects were evaluated by DNA, collagen, and glycosaminoglycan (GAG) quantification and hematoxylin and eosin and immunofluorescence staining to determine the absence of nucleic acids and preservation of heart ECM components. Similar to the native group, the scCO(2)-EtOH group contained more ECM components such as collagen, GAGs, collagen I, laminin, and fibronectin and angiogenic factors including vascular endothelial growth factor, fibroblast growth factor, and platelet-derived growth factor and others in comparison to the detergent group. In addition, to estimate angiogenesis of the dECM hydrogels, the neutralized dECM solution was injected in a rat subcutaneous layer (n = 6 in each group: collagen, scCO(2)-EOH, and detergent group), after which the solution naturally formed gelation in the subcutaneous layer. After 3 days, the gels were harvested and estimated by immunofluorescence staining and the Image! program for angiogenesis analysis. Consequently, blood vessel formation and density of vWF and alpha-SMA in the scCO(2)-EtOH group were significantly greater than that in the collagen group. Here we suggest that heart-derived decellularized extracellular matrix (dECM) with scCO(2)-EtOH treatment is a highly promising angiogenic material for healing in ischemic disease. Statement of Significance Supercritical carbon dioxide (scCO(2)) in a supercritical phase has low viscosity and high diffusivity between gas and liquid properties and is known to be affordable, non-toxic, and eco-friendly. Therefore, scCO(2) extraction technology has been extensively used in commercial and industrial fields. Recently, decellularized extracellular matrix (dECM) was applied to tissue engineering and regenerative medicine as a scaffold, therapeutic material, and bio-ink for 3D printing. Moreover, the general decellularization method using detergents has limitations including eliminating tissue-derived ECM components and disrupting their structures after decellularization. To overcome these limitations, heart tissues were treated with scCO(2)-EtOH for decellularization, resulting in preserving of tissue due to the various ECM and angiogenic factors derived. In addition, initiation of angiogenesis was highly induced even after 3 days of injection. (C) 2017 Published by Elsevier Ltd on behalf of Acta Materialia Inc.
Keywords: EXTRACELLULAR-MATRIX; GROWTH-FACTOR; MYOCARDIAL-INFARCTION; HYDROSTATIC-PRESSURE; RAT MODEL; TISSUE; STERILIZATION; SCAFFOLD; CELLS; EXTRACTION